Effects of 2 types of activation protocols based on postactivation potentiation on 50-m freestyle performance - Cuenca-Fernández, F.; Ruiz-Teba, A.; López-Contreras, G.; Arellano, R. (The Journal of Strength and Conditioning Research, 2020)
Postactivation potentiation (PAP) is a phenomenon which improves muscle contractility, strength, and speed in sporting performances through previously applied maximal or submaximal loads on the muscle system. This study aimed to assess the effects of 2 types of activation protocols based on PAP, on sprint swimming performance. A repeated-measures design was used to compare 3 different scenarios before a 50-m race. First, all of the participants performed a standard warm-up (SWU), consisting of a 400-m swim followed by dynamic stretching. This protocol acted as the control. Subsequently, the swimmers were randomly assigned into 2 groups: the swimmers in the first group performed the SWU followed by a PAP one-repetition maximum warm-up (RMWU), consisting of 3 "lunge" and 3 "arm stroke" repetitions, both at 85% of the one-repetition maximum. The swimmers in the second group performed the SWU followed by a PAP eccentric flywheel warm-up (EWU), consisting of one set of 4 repetitions of exercises of both the lower and upper limbs on an adapted eccentric flywheel at the maximal voluntary contraction. The time required for the swimmers to swim 5 and 10 m was shorter with the PAP protocols. The swimming velocity of the swimmers who underwent the EWU and RMWU protocols was faster at 5 and 10 m. The best total swimming time was not influenced by any of the protocols. When isolating swimming (excluding start performance and turn), best time was achieved with the SWU and RMWU compared with EWU (SWU: 20.86 ± 0.95 seconds; EWU: 21.25 ± 1.12 seconds; RMWU: 20.97 ± 1.22 seconds). In conclusion, a warm-up based on PAP protocols might exert an influence on performance in the first meters of a 50-m race. Nevertheless, other factors, such as fatigue, could modify swimming patterns and yield results contradictory to those of the desired task.